2016
DOI: 10.21082/ijas.v9n1.2008.p19-23
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fruit Bagging, Sanitation, and Yellow Sticky Trap to Control Thrips on Mangosteen

Abstract: Scars on mangosteen fruits caused by thrips are the most prominent constraint in Indonesian export of mangosteen. Most of the exported mangosteen are rejected due to scar appearance. This research aimed to study the effects of fruit bagging, sanitation, and sticky trap application on the scar intensity on mangosteen. The research was conducted at a farmer's polycultured mangosteen orchard in Lima Puluh Kota, West Sumatra, Indonesia from September 2006 to February 2007. The mangosteen trees were cultured with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Few studies have been performed on the use of fruit bagging in reducing the incidence of thrips pests: Affandi et al (2008) found a reduction in scarring of mango fruits (caused by an unspecified species of thrips) of 32-42% in Indonesia using double-layered bags of plastic and paper. Karar et al (2019) found that harvested fruits of mango in closed paper bags (brown paper inner black and butterwet resistant/ greaseproof -paper) were 100% free of (unspecified) thrips in Pakistan.…”
Section: Fruit Baggingmentioning
confidence: 99%
“…Few studies have been performed on the use of fruit bagging in reducing the incidence of thrips pests: Affandi et al (2008) found a reduction in scarring of mango fruits (caused by an unspecified species of thrips) of 32-42% in Indonesia using double-layered bags of plastic and paper. Karar et al (2019) found that harvested fruits of mango in closed paper bags (brown paper inner black and butterwet resistant/ greaseproof -paper) were 100% free of (unspecified) thrips in Pakistan.…”
Section: Fruit Baggingmentioning
confidence: 99%
“…Few studies have been performed on the use of fruit bagging in reducing the incidence of thrips pests: Affandi et al. (2008) found a reduction in scarring of mango fruits (caused by an unspecified species of thrips) of 32–42% in Indonesia using double‐layered bags of plastic and paper. Karar et al.…”
Section: Thrips Palmimentioning
confidence: 99%
“…Few studies have been performed on the use of fruit bagging in reducing the incidence of thrips pests: Affandi et al (2008) found a reduction in scarring of mango fruits (caused by an unspecified species of thrips) of 32-42% in Indonesia using double-layered bags of plastic and paper. Karar et al (2019) found that harvested fruits of mango in closed paper bags (brown paper inner black and butterwet resistant/greaseproofpaper) were 100% free of (unspecified) thrips in Pakistan.…”
Section: Fruit Baggingmentioning
confidence: 99%
“…Few studies have been performed on the use of fruit bagging in reducing the incidence of thrips pests: Affandi et al. (2016) found a reduction in scarring of mango fruits (caused by an unspecified species of thrips) of 32–42% in Indonesia using double‐layered bags of plastic and paper. Karar et al.…”
Section: Thrips Palmimentioning
confidence: 99%